(untitled) (ModaPalavra e-periódico, 2008)
The segment of infantile clothing in Brazil has presented a sped up growth, today the companies pressured for these consumers and recognizing the necessity to have an innovative product that surprises its target public, searching to add information to infantile clothing. The present article approaches the question of the evolution of infantile clothing and the concern with the questions associates to the usability of this product. Considering that the usability is understood as the evaluation of flexibility and bigger interaction using product, having in it views at the necessities of the user.